Taxonomy – a tool determining the direction of transformation in heat engineering - Śniegowski, Maciej (Instal, 2022)
The taxonomy will indicate which operating and investment activities qualify as environmentally sustainable to help the investor create business models in line with the goals of the energy transformation. The article presents the types of activities for the energy sector that are included in the taxonomy. The focus was on selected 3 types of activities and described the objectives and criteria that must be met by these activities in order to be considered environmentally sustainable.
Keywords: taxonomy; environmentally sustainable activity; heating